CROWDEDNESS DAN SAFETY MEASURES PADA RESTAURANT PATRONAGE CHOICES SELAMA MASA PANDEMI COVID-19 - Giovani Natasha; Sharon Trisha; Agung Harianto (Jurnal Manajemen Perhotelan, 2022)
This study aims to determine which attributes of crowdedness and safety measures are the customer's choices when determining restaurant patronage choices during the COVID-19 pandemic. The researcher used descriptive statistical analysis, and cross tabulation analysis between gender and the choice of restaurant patronage, and Google Form. Analysis of dine-in on patronage choices, respondents chose low crowdedness by providing distance between tables, while take away and leave on patronage choices, respondents chose high crowdedness with no safety measure. Not using in-between table also widely applied in restaurants because it can cause distance. In terms of crowds, perceptions of safety, comfort, popularity and quality also determine the level of crowds. The results of the crosstabulation analysis show that women are more concerned with safety measures and avoiding crowds, and men are more flexible and adaptable. Abstrak Penelitian ini bertujuan untuk mengetahui atribut crowdedness dan safety measure mana yang menjadi pilihan pelanggan saat menentukan restaurant patronage choices selama pandemi COVID-19. Peneliti menggunakan analisa statistik deskriptif, dan analisa tabulasi silang antara jenis kelamin dengan pilihan patronase restoran, serta Google Form. Dari 190 data, hasil analisa dine in pada patronage choices, responden memilih kondisi low crowdedness dengan memberikan jarak antar meja, sedangkan pilihan take away dan leave pada patronage choices, responden memilih high crowdedness dengan no safety measure. Pemberian tanda silang pada beberapa meja juga banyak diterapkan di restoran karena bisa menimbulkan jarak. Dalam segi keramaian, persepsi keamanan, kenyamanan, popularitas dan kualitas juga menentukan tingkat keramaian. Hasil analisa tabulasi silang menunjukkan wanita lebih mementingkan langkah-langkah keamanan dan menghindari keramaian, serta pria lebih fleksibel dan mudah beradaptasi.